Young couple expecting first child among new students at UUM - Borneo Post, (Kuching) (Borneo Post (Kuching), 2015)
Sintok, Kedah: A young couple expecting their first child are among those who registered as new students at Univesiti Utara Malaysia (UUM) campus here, yesterday.